Computer-Aided Design and Simulation of Spatial Opto-Mechatronic Interconnect Devices - Zeitler, Jochen; Reichle, Andreas; Franke, Jörg; Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert (26th CIRP Design Conference, 2016, 2016)
Optical technologies become increasingly important in modern sensor and communication applications. Nevertheless, manufacturing and design methods in the field of spatial opto-electronics have not been investigated intensively yet. A new approach is to print polymer waveguides on spatial carriers to use the full design freedom of opto-mechatronic assemblies. Up to now, no specific design tools and validation methods are available. The article describes possible technology-specific methods for designing spatial opto-mechatronic applications with the focus on computer-aided design (CAD) and raytracing simulation of spatial waveguides.
Keywords: computer-aided design (CAD); design method; optical communication; opto-electronics; simulation

Technical Modelling Approach for Spatial Integrated Optomechatronic Products - Zeitler, Jochen; Reitberger, Thomas; Reichle, Andreas; Backhaus, Carsten; Lindlein, Norbert; Franke, Jörg (Procedia CIRP, Volume 84, 2019)
In the age of digitalization, the amount of data generated and transferred continues to increase dramatically. To increase the usability of this data it must be accessible with sufficient transmission bandwidth. Optical signals are already being used for transmitting data over long distances and high bandwidths, as this enables fast and low-loss data transmission. This trend is now also continuing in smaller scales of data transmission. Consequently, even highly integrated electrical circuits must be supported with optical components. Therefore, completely new research approaches for the product development of spatially integrated optical waveguides are necessary. The polymer-based aerosol jet printing represents a promising method to print optical waveguides on 3D circuit carriers. For this reason, the Research Group for Module Integrated Bus Systems deals with topics related to product development and production of such systems. A focus is to customize the design and associated modelling tasks accordingly. Thus, it is essential to create methodical approaches for a digital representation of waveguides and their production processes in order to map the physical behavior and to predict their manufacturability. Current studies show that integrated engineering approaches with removed boundaries among engineering domains are preferable to traditional engineering approaches. Consequently, novel engineering tools are needed for modelling the geometric as well as the physical properties of optical waveguides with the possibility to integrate specific design rule checks. The presented modelling approach in this paper provides/supports the creation of exact digital models without discontinuities through unnecessary interfaces. This article presents a method for a powerful computer-aided modelling environment that enables the design of models that are capable of representing and validating logical relationships among optoelectronic networks, but also considers challenges resulting from spatial geometric characteristics as well as restrictions from manufacturing and physic
Keywords: Computer aided design (CAD); Product development; Optomechatronics